2003
DOI: 10.5144/0256-4947.2003.194
|View full text |Cite
|
Sign up to set email alerts
|

Cowper's Syringocele (Cyst of the Bulbar Urethra): A Case Report and Literature Review

Abstract: A Tayib, H Mosli, M Atwa, Cowper's Syringocele (Cyst of the Bulbar Urethra): A Case Report and Literature Review. 2003; 23(3-4): 194-195 Cowper's glands are two bulbourethral glands that lie superior to the perineal membrane and are invested in the broad base of the external urethral sphincter muscles.1 During sexual excitement these glands secrete clear mucous into the bulbous urethra. A syringocele is a deformity in the male urethra in which there is a distention of the bulbourethral Cowper's glands. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…123 Although incidence is not widely reported, we found that 290 (2.6%) of 11,069 patients underwent orchiectomy. 4,11,17,20,22,23,[26][27][28][41][42][43]47,50,[53][54][55][56]60,66,70,79,91,95,98,101,103,104,109,112 Yanar et al 60 found that when orchiectomy was performed, using surgeon judgment, 100% of final histologic analysis showed normal testicular tissue with no signs of FG-supporting the principle that orchiectomy is often not necessary. There are no guidelines about the best timing to perform orchiectomy when needed.…”
Section: Orchiectomymentioning
confidence: 99%
See 1 more Smart Citation
“…123 Although incidence is not widely reported, we found that 290 (2.6%) of 11,069 patients underwent orchiectomy. 4,11,17,20,22,23,[26][27][28][41][42][43]47,50,[53][54][55][56]60,66,70,79,91,95,98,101,103,104,109,112 Yanar et al 60 found that when orchiectomy was performed, using surgeon judgment, 100% of final histologic analysis showed normal testicular tissue with no signs of FG-supporting the principle that orchiectomy is often not necessary. There are no guidelines about the best timing to perform orchiectomy when needed.…”
Section: Orchiectomymentioning
confidence: 99%
“…*An estimated 61 of 108 studies quantify patients who underwent culture 4,8,11,12,17,18,20,21,[23][24][25]30,31,34,[36][37][38][41][42][43][44][45][46]49,50,52,56,57,59,60,63,69,72,76,77,80,82,[84][85][86][87][89][90][91][93][94][95][96][98][99][100][101][102]…”
mentioning
confidence: 99%
“…Cowper's gland develops from the urogenital tubercle, derived from the pericloacal mesoderm, for which androgens play a pivotal role [ 4 ]. They are located in the wide base of the external urethral sphincter muscles in the deep perineal pouch, posterolateral to the membranous urethra, and superior to the perineal membrane [ 5 - 6 ]. The Cowper's gland ducts open into the bulbous urethra in the superficial perineal pouch by penetrating the perineal membrane [ 7 ].…”
Section: Reviewmentioning
confidence: 99%